Performance of water-leached coal bottom ash as catalyst in Thermogravimetric Analyser (TGA) biomass gasification - Patrick, D.O. (Italian Association of Chemical Engineering - AIDIC, 2017)
The catalytic gasification of palm kernel shell in Thermogravimetric Analyser (TGA) with a mass spectrometer setup using water-leached coal bottom ash (CBA) is presented in this research work. The leaching temperature, time and liquid volume to solid (L/s) ratio were varied in the design of experiment using response surface methodology (RSM). Effects of the interaction between these parameters were plotted in 3D surface plots. Maximum H2 and syngas contents obtained in the steam gasification at 700 °C were 40.78 vol and 70.94 vol. CBA leached for 6.5 h at 66.20 °C and L/s ratio of 4 with 81.26 Å pore width, 0.004 cm2/g pore volume and 1.90 m2/g BET surface area produced the highest H2 content while that treated for 6.5 h at 45 °C and L/s ratio of 2.59 with 50.01 Å pore width, 0.004 cm2/g pore volume and 3.0583 m2/g BET surface area produced the highest syngas content. The CO2 content of the gas produced was less than 2 vol. L/s ratio is the most influential of the leaching parameters affecting H2 and syngas production. Copyright © 2017, AIDIC Servizi S.r.l.